2021
DOI: 10.1007/s00415-021-10883-1
|View full text |Cite
|
Sign up to set email alerts
|

White matter connectivity networks predict levodopa-induced dyskinesia in Parkinson’s disease

Abstract: Background Although levodopa-induced dyskinesia-relevant white matter change has been evaluated, it is uncertain whether these changes may reflect the underlying predisposing conditions leading to the development of levodopa-induced dyskinesia. Objective To elucidate the role of white matter connectivity networks in the development of levodopa-induced dyskinesia in drug-naïve Parkinson's disease. Methods We recruited 30 patients who developed levodopa-induced dyskinesia within 5 years from MRI acquisition (vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…It is well known that the baseline nigrostriatal dopamine level is the main contributor to the development of LID and WO, 42,43 although other clinical and imaging parameters are also contributing factors. [44][45][46][47] This may be because DHPs have no neuroprotective effects on nigral dopaminergic neurons or their related clinical characteristics, which may be in agreement with the results of the isradipine trial focusing on the progression of nigral dopamine-related motor symptoms. 12 Rather, it is speculated that DHPs may have a beneficial effect on the extranigral system.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It is well known that the baseline nigrostriatal dopamine level is the main contributor to the development of LID and WO, 42,43 although other clinical and imaging parameters are also contributing factors. [44][45][46][47] This may be because DHPs have no neuroprotective effects on nigral dopaminergic neurons or their related clinical characteristics, which may be in agreement with the results of the isradipine trial focusing on the progression of nigral dopamine-related motor symptoms. 12 Rather, it is speculated that DHPs may have a beneficial effect on the extranigral system.…”
Section: Discussionsupporting
confidence: 53%
“…Contrary to expectations, we found that DHPs did not have beneficial effects on the nigrostriatal dopaminergic density at diagnosis and longitudinal motor prognosis. It is well known that the baseline nigrostriatal dopamine level is the main contributor to the development of LID and WO, 42,43 although other clinical and imaging parameters are also contributing factors 44‐47 . This may be because DHPs have no neuroprotective effects on nigral dopaminergic neurons or their related clinical characteristics, which may be in agreement with the results of the isradipine trial focusing on the progression of nigral dopamine‐related motor symptoms 12 .…”
Section: Discussionmentioning
confidence: 69%
“…In addition, a study using network-and degreebased statistics observed stronger connectivity within the four subnetworks consisting of edges centered on the superior frontal gyrus, putamen, insular, and precentral gyrus. 57 Taken together, these studies showed that altered signals originating from basal ganglia might result in a reinforced motor drive to cortical activity and ultimately trigger involuntary movements. 58,59 The altered FC between SNpc and putamen found in our study could relate to the excessive activity in LID.…”
Section: Discussionmentioning
confidence: 89%